Cu2O thin films deposited by spray pyrolysis using diethanolamine and L-ascorbic acid as reducing agents. (August 2022) - Ugalde-Reygadas, M.; Moreno-Regino, Valeria D.; Torres-Castanedo, Carlos G.; Bedzyk, Michael J.; Castanedo-Pérez, Rebeca; Torres-Delgado, Gerardo
Abstract: Cu2 O thin films are of great interest due to their diverse applications. Spray pyrolysis is a low-cost and straightforward technique among the different methods used to deposit them. Precursor solutions using D -glucose as reducing agent and copper acetate have mainly been used. However, the D-glucose's remaining subproduct can detriment the films' properties and use in devices. In this work, precursor solutions using diethanolamine (DEA) or L -ascorbic acid (AA) as reducing agents to deposit Cu2 O thin films are used for the first time. The effect on the structural, morphological, electrical, and optical properties of Cu2 O thin films is shown for 0.25 M of DEA and 0.1 M of AA, which were the optimal molar concentrations to obtain homogeneous solutions, with 0.04 M of copper nitrate. The deposition temperature ( T d ) determines the formation of Cu2 O single phase. XRD analysis reveals films only constituted by Cu2 O using DEA in the 280 ° C ≤ T d ≤ 310 ° C and AA in the 280 ° C ≤ T d ≤ 290 ° C ranges. These deposition temperatures are lower than the reported values (∼ 330 °C) using the same copper salt and glucose. This fact is associated with the reducing character of both agents since the obtained precursor solutions lead to an in-situ reduction. In addition, the films show minimum organic impurities content associated with the low volatilization temperature of the DEA and AA, which is desirable for their application in devices. The calculated bandgap energy (2.3–2.4 eV) for both types of films corresponds to nanocrystalline Cu2 O. However, using L -ascorbic acid resulted in thin films with the lowest resistivity (10 2 Ω cm ), attributed to an improvement in the crystallinity. Graphical Abstract: Electrical resistivity for both DEA and AA films (right) as a function of deposition temperature. The reduction of deposition temperatures using DEA and AA instead of glucose is attributed to the in situ reduction process, detected from each precursor solution absorption bands (left). Also (as comparative), resistivity values reported by Osorio-Rivera et al. Highlighted zones show the presence of Cu2 O, CuO, and the mixture, indicating first the predominant phase. ga1 Highlights: Cu2 O thin films at low substrate temperature (∼230 °C) by spray pyrolysis (SP). Effect of L -ascorbic acid as reducing agent on Cu2 O precursor solution sprayed. Effect of diethanolamine as reducing agent on Cu2 O precursor solution sprayed. Cu2 O nanocrystalline films obtained by SP with low resistivity of 10 2 Ω-cm. Low organic content in Cu2 O films by chemical route.